STUDYING METHODS TO MONITOR AND EVALUATE THE SAFETY OF DRUGS POST-MARKET, INCLUDING ADVERSE DRUG REACTIONS - Mohammed Nuwaymi Toma Aljaberi, Asma Ibrahim Al Zayn, Talal Tail Alsulami, Mohammad Saleh Abdullah Alamri, Saad Mohammed Awwadh Alshalwi, Fahad Noor Faleh Alasadi, Nader Essa Subayyil Alotaibi and Ali Abdullah Ahmed Alqarni, (Chelonian Research Foundation, 2024)
The safety of drugs post-market is a crucial aspect that must be carefully monitored and evaluatedto ensure the well-being of patients. Adverse drug reactions (ADRs) can have seriousconsequences, and it is important to have effective methods in place to detect, assess, and managethese reactions. This paper explores various studying methods used to monitor and evaluate thesafety of drugs post-market, with a specific focus on adverse drug reactions. The methodology,results, and discussion of these methods are presented to provide a comprehensive overview of thetopic